Financial Literacy and FinTech Access as Drivers of Financial Inclusion and Business Sustainability among Women Entrepreneurs - Lestari, Elissa Dwi; Kurniasari, Florentina; Loebiantoro, Ika Yanuarti (Indonesian Journal of Sustainability Accounting and Management, 2025)
Women MSME actors in Indonesia play an essential role in economic growth but still face challenges in accessing formal financial services equally. Gaps in financial knowledge, limited digital access, and structural barriers hinder equitable and sustainable financial inclusion. In response, FinTech offers a promising pathway to bridge these disparities. This study investigates the effect of financial literacy on FinTech-based financial access and its subsequent impact on financial inclusion and business sustainability among women entrepreneurs. It further explores the mediation role of FinTech access as a mediator that has rarely been examined in the context of women entrepreneurs in emerging countries. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS- SEM). The sample comprised 345 women MSME owners who had operated their businesses for at least one year and used FinTech services. The results show that financial literacy enhances FinTech access and financial inclusion. Access to digital finance mediates the link between financial literacy and inclusion, emphasizing the need for enabling factors beyond knowledge. Lastly, financial inclusion significantly drives women entrepreneurs’ business sustainability. This study presents a novel perspective that views financial literacy as a personal capability and FinTech access as a strategic resource using Capability Theory and the Resource-Based View. This dual-theoretical perspective emphasizes skills and systems’ interconnectedness in inclusive entrepreneurship. The findings underscore the relevance of financial acumen and inclusive digital infrastructure for women’s formal finance involvement and business sustainability.